WILL INDONESIA EMPLOY THE KEYNESIAN THEORY TO PROTECT ITS ECONOMY IN THE CASE OF A GLOBAL RECESSION IN 2023? - Fridayani, Helen Dian; Setiawan, Anang (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2023)
The World once more experienced an economic catastrophe in 2020, just 12 years after the global financial crisis. The global pandemic known as Covid-19 is the cause of the current crisis, which has an entirely different impact on the economy than the previous global financial crisis. The effect of the recession this time on Indonesia will be through three things, such as exports, investment, and purchasing power. Meanwhile, the thing that will be most felt by individuals is losing their jobs, although it is predicted that it will not be too significant either. Seeing this reality, the government especially Indonesia should immediately improve in facing the threat of global economic recession. A bleak period marked by negative economic growth for two consecutive quarters cannot be underestimated. In urgent times, the government must at the same time maintain people's purchasing power, control inflation, increase exports, and encourage investment growth. The government must not be slow to act because the signs of recession are in sight. This research is qualitative research that is a literature study (library research) that uses books and other literature as the main object. The result of this study is in maintaining domestic economic stability, Indonesia still refers to the Keynesian theory which suggests that the government must intervene in economic activities in a country